ANALISIS PERBANDINGAN KEANDALAN SISTEM JARINGAN DISTRIBUSI BERKONFIGURASI RADIAL DAN LOOP MENGGUNAKAN METODE RIA (RELIABILITY INDEX ASSESSMENT) - H.R.B Moch Gozali; Suprihadi Prasetyono; Dimas Oktasya Eka Kumala Putra (Jurnal Arus Elektro Indonesia, 2020)
Electrical energy is a very important requirement for human life. The supply of electrical energy itself consists of electricity generation, power transmission and distribution. In the distribution of electricity, there are several networks that function to distribute electrical energy to customers, the majority of which are network configuration, namely radial and loop. In order to maintain the continuity of the distribution of electrical energy, a good level of reliability is required. In order to determine the reliability of the distribution system, the reliability index is determined, namely SAIFI, SAIDI and CAIDI. Several methods that can be used to find a distribution system reliability index include the RIA (Reliability Index Assessment) method, which is an approach used to predict disturbances in a distribution system based on the system topology and data regarding component reliability. In this study, we compared two configurations using one feeder, namely the Giri feeder which is assumed to have a radial configuration and a loop configuration. By using the RIA (Reliability Index Assessment) method on a Giri feeder with a radial configuration, the SAIFI reliability index is obtained at 1.595 times / year, SAIDI is 12.8092 hours / year, CAIDI is 8.0309 hours / year, while for a feeder with a loop configuration the SAIFI value is equal to 1,651 times / year, SAIDI is 1,7276 hours / year, CAIDI is 1,0416 hours / year. Keywords — Reliability Index, Distribution System, Reliability Index Assessment, SAIFI, SAIDI, CAIDI